Kin relationality and ecological belonging: a cultural psychology of Indigenous transcendence - Celidwen, Yuria; Keltner, Dacher (Frontiers in Psychology, 2023)
In this article, we consider prosociality through the lens of an Indigenous "ethics of belonging" and its two constitutive concepts: kin relationality and ecological belonging. Kin relationality predicates that all living beings and phenomena share a familial identity of interdependence, mutuality, and organization. Within the value system of ecological belonging, an individual's identity is constituted in relation to the natural environment, centered on the sentiments of responsibility and reverence for Nature. We detail how Indigenous perspectives upon prosociality differ from Western scientific accounts in terms of the motives, scope, and rewards of altruistic action. Grounded in this understanding, we then profile three self-transcendent states, compassion, gratitude, and awe, and their similarities across Indigenous and Western approaches, and how kin relationality and ecological belonging give rise to cultural variations.We consider convergent insights across Indigenous and Western science concerning the role of ritual and narrative and the cultural cultivation of kin relationality and ecological belonging. We conclude by highlighting how these two core concepts might guide future inquiry in cultural psychology.